(untitled) (Research, Society and Development, 2021)
Objective: to describe the difficulties of planned home birth in Brazil evidenced in the scientific production of nursing. Methodology: Systematic review using the descriptors Home Birth; Obstetric Nursing and Nursing Care. The survey of the articles was done in three databases: Scientific Eletronic Library Online (SCiELO), Medical Literature Analysis and Retrievel System Online (Medline) e Literatura Latino-americana e do Caribe em Ciências da Saúde (LILACS), guided by the guided question: What are the difficulties of planned homebirth in Brazil? Studies published from 2010 to March 2021 were included. Results: In total, 22 articles were submitted to review review and all were subdivided into three categories: the current paradigm, the absence of public policy to support planned home birth and the gap in the production and dissemination of knowledge. Final considerations: This review points out the current paradigm, which is technocratic, biomedical, interventionist or curative, as difficulties in planned home births in Brazil; the absence of public policy related to planned home birth; and the gap in the production and dissemination of specific knowledge, with developments that reach the training of specialists.